2009
DOI: 10.1177/1082013208100507
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Acoustic Firmness and Magness Taylor Firmness in Royal Gala and Golden Smoothee Apples

Abstract: This study aimed to evaluate apple firmness measured using both the penetrometer and acoustic methods. The methodologies were applied to Royal Gaya and Golden Smoothee apples (Malus domestica. Borkh) harvested from 12 different orchards in Catalonia (Spain), on six different dates, and over three seasons. The relationship between firmness and physicochemical quality parameters was analyzed at harvest and post-harvest. The results obtained showed a noticeable correlation between Magness Taylor firmness and acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…Correlations between EI i and MF were affected by the fruit variety in our study, and similar results were found by Shmulevich et al (2003) and Molina-Delgado et al (2009). This was because Magness-Taylor firmness and acoustic firmness reflected different aspects of fruit texture.…”
Section: Resultssupporting
confidence: 89%
“…Correlations between EI i and MF were affected by the fruit variety in our study, and similar results were found by Shmulevich et al (2003) and Molina-Delgado et al (2009). This was because Magness-Taylor firmness and acoustic firmness reflected different aspects of fruit texture.…”
Section: Resultssupporting
confidence: 89%
“…C rispness is one of the most important sensory attributes required by consumers in an apple (Daillant-Spinnler et al, 1996). The majority of routine texture measures in apple use either a manual or constant rate Magness-Taylor-type penetrometer (Magness and Taylor, 1925;Molina-Delgado et al, 2009) or a non-destructive acoustic resonance technology (De Baerdemaeker, 1988).…”
mentioning
confidence: 99%
“…Other researchers have also observed similar weak correlations (Armstrong et al, 1990;Molto et al, 1998;Shmulevich et al, 2003;Molina-Delgado et al, 2009). They concluded that the reasons for the weak correlations might be because the F max (Magness-Taylor firmness) and the vibration parameters seemed to respond to different physical properties and the variety seemed to influence the correlation coefficient.…”
Section: Correlations With Firmness Variablesmentioning
confidence: 78%
“…Firmness provides information about the maturity, quality, shelf life and likelihood of possible physiological disorders (Galili et al, 1998;Molina-Delgado et al, 2009), which is very important for the grower, packer and retailer during the picking, grading, transporting, storing and distributing operations (Armstrong et al, 1990;Abbott and Liljedahl, 1994;Mirzaee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%